Performance Evaluation of After Sale Service in Automotive Industry by Data Envelopment Analysis - Habibi, Amir Reza (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
In this decade, automotive industry has become second big industry in Iran after oil while more than 1 million and 350 thousand cars are produced yearly by different companies and have influenced in most of Iranian’s living and has been considered by government due to sanction against Iran, appreciation of prices and dissatisfaction of customers in after sale services. This study will investigate 88 after sale service dealers belong to Kerman Motor Co. in all over Iran as a sample of the entire automotive industry in Iran. All data (number of customers, human resources, education, equipment, providing pieces and process as 6 inputs and stopped cars more than 48 hours in the repair shop, reworked cars, and customer satisfaction as 3 outputs) has been gathered during 2016-2017 observation of all dealers. Data Envelopment Analysis (DEA) has been applied as one of the most common evaluation methods for measuring the efficiency of performance of each dealer. Contrary to Iran Standard Quality Institute (ISQI) which sends inspectors to all dealers from all companies to evaluate them yearly by a solid framework and without considering the differences in facilities and population in various regions of Iran, DEA has been utilized in this study to evaluate the dealer’s efficiencies and rank them by their own capacities and potentials. CCR model as one of the basic models of DEA has been used in this study due to its more rigid and inflexible essence in comparison to other models. All weights assigned to inputs/outputs will be analyzed to find out most significant index which is effects inefficiency, also inefficient dealers are compared to efficient dealers with most similar for recognizing the weakness and an improvement plan will be presented for giving insight for inefficient units to be improved at the end.

ÖZ: Son on yıl içerisinde İran’da yılda 1 milyon 350 bin araç farklı şirketler tarafından üretiliyor ve bu esnada otomotiv endüstrisi petrol’den sonra İran’da ikinci büyük endüstri haline gelmiştir. Fakat, Dünya’nın İran devletine uyguladığı yaptırımlar yüzünden satış sonrası servislerde (parça değişimi, tamirat, vs.) bir çok İran’lı vatandaşın yüksek fiyatlar karşısında memuniyetsiz olduğu gözlemlenmiştir. Bu çalışma İran’ın otomotiv endüstrisini örneklemek amacıyla İran’da bulunan Kerman Motor’s şirketine ait olan 88 araç servisinde yapılmıştır. Toplanan veri (müşteri sayısı, insan kaynakları, eğitim, ekipman, parça temini ve işlem süresi olarak 6 girdi verisi ve 48 saatir tamirhanede bulunan durmuş araçlar, yeniden çalıştırılmış araçlar ve müşteri memnuniyeti olarak 3 çıktı verisi) 2016-2017 yılları arasında araç servislerini gözlemleyerek toplanmıştır. Her araç servisindeki verimilik performansını ölçmek için oldukça yayın bir metod olan Veri Zarflama Analizi (VZA) kullanılmıştır. İran Stadart Kalite Denetleme Enstitüsü (İSKD) İran’da bulunan bütün araç şirketlerine ait araç servislerine tesis farkı, bölgelerindeki nüfüsların yoğunluğunu gözetmeksizin denetim yapmak amacıyla gözetmen göndermektir buna karşın, VZA araç servislerinin verimliğini ölçerken araç servislerini kapasitelerini ve potansiyellerini göz önüne alarak sınıflandırma yapmaktadır. Daha sabit ve kararlı sonuç almak ve literatürde kullanılmış diğer modellerle kıyas yapabilmek adına VZA ait olan CCR modeli bu çalışmada kullanılmıştır. Girdi/Çıktılara atanan bütün ağırlıklar verimliliği etkilyen en dikkate değer endeksi bulmak için analiz edilecektir. Ayrıca, verimsiz araç servislerinin zayıf noktalarını teşhis etmek için verimli araç servisleri ile karşılaştırılacak ve verimsiz olan araç servisleri için bir iyileştirme planı yapılarak daha sonra nasıl verimli hale gelebilcekleri gösterilecektir.
Master of Science in Industrial Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2019. Supervisor: Assist. Prof. Dr. Sahand Daneshvar.
Keywords: Industrial Engineering; Industrial productivity; Automotive industry; Data Envelopment Analysis (DEA); Performance; Efficiency; Significant index